Pengaruh Financial Distress, Kualitas Audit, dan Generalist Skills CEO terhadap Opini Audit Going Concern - Aisyah, Nurul; Sutoyo, Sutoyo (Politeknik Negeri Jember, 2025)
This research analyzes the effect of financial distress, audit quality, and CEO generalist skills on going concern audit opinions for energy sector companies listed on the Indonesia Stock Exchange from 2021 to 2024. The study sample encompasses oil and gas firms selected through a purposive sampling technique, resulting in 14 companies observed over four years, which provided 56 data observations Logistic regression analysis is employed to examine the effects of financial distress and CEO generalist skills on going concern audit opinions. Meanwhile, the effect of audit quality is tested using Fisher’s Exact Test due to the presence of a complete separation phenomenon. The results indicate that financial distress has a positive and significant effect on going concern audit opinions, audit quality has a negative and significant effect, while CEO generalist skills have no significant effect. These findings suggest that financial conditions and audit quality are key determinants of going concern audit opinions in energy sector companies.